2014
DOI: 10.1155/2014/807054
|View full text |Cite
|
Sign up to set email alerts
|

Unpredictable Nature of Tolvaptan in Treatment of Hypervolemic Hyponatremia: Case Review on Role of Vaptans

Abstract: Hyponatremia is one of the most commonly encountered electrolyte abnormalities occurring in up to 22% of hospitalized patients. Hyponatremia usually reflects excess water retention relative to sodium rather than sodium deficiency. Volume status and serum osmolality are essential to determine etiology. Treatment depends on several factors, including the cause, overall volume status of the patient, severity of hyponatremic symptoms, and duration of hyponatremia at presentation. Vasopressin antagonists like tolva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
25
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 12 publications
0
25
0
4
Order By: Relevance
“…Only two of those cases have been published (S.A.A. Harb and C. Alraies, unpublished data) (73). However, some other factors could have contributed to PNa overcorrection in the published cases.…”
Section: Vasopressin Receptor Antagonists (Vaptans)mentioning
confidence: 94%
“…Only two of those cases have been published (S.A.A. Harb and C. Alraies, unpublished data) (73). However, some other factors could have contributed to PNa overcorrection in the published cases.…”
Section: Vasopressin Receptor Antagonists (Vaptans)mentioning
confidence: 94%
“…Man beachte, dass auch im Kontrollarm einer Metaanalyse zu Vaptanen [6] Auch unter Tolvaptan-Monotherapie, insbesondere bei nicht bestimmungsgemäßem Gebrauch, kann es aufgrund seiner aquaretischen Potenz im Rahmen einer überschnellen Korrektur zu einem ODS kommen. Dies wird an einem "gut" dokumentierten ODS-Fall nach extremer Fehlbehandlung mit Tolvaptan deutlich [18]. Trotz täglicher Dokumentation der Natriumwerte und der in diesem Fall erheblichen Ausfuhr wurde mit zunehmendem Natriumanstieg die Tolvaptan-Therapie nicht abgesetzt oder reduziert, sondern sogar grob fehlerhaft gesteigert, was schließlich eine schwere Hypernatriämie und ein ODS zur Folge hatte [18].…”
Section: Osmotisches Demyelinisationssyndromunclassified
“…Dies wird an einem "gut" dokumentierten ODS-Fall nach extremer Fehlbehandlung mit Tolvaptan deutlich [18]. Trotz täglicher Dokumentation der Natriumwerte und der in diesem Fall erheblichen Ausfuhr wurde mit zunehmendem Natriumanstieg die Tolvaptan-Therapie nicht abgesetzt oder reduziert, sondern sogar grob fehlerhaft gesteigert, was schließlich eine schwere Hypernatriämie und ein ODS zur Folge hatte [18].…”
Section: Osmotisches Demyelinisationssyndromunclassified
“…11,12 However, so far only one case of human ODS has been published in which the use of vaptans unfortunately led to an excessive correction gradient (66 mEq/l over 72 h) along with hyperosmolarity. 13 Another option for the treatment of hyponatremia is urea, and our team has reported that urea is effective in correcting euvolemic and even hypervolemic hyponatremia. 14,15 Interestingly, urea, through an unclear mechanism, acts as a cryoprotectant and an osmoprotectant in amphibians.…”
mentioning
confidence: 99%